(untitled) (Scientific journal of the Fergana State University, 2024)
It is known that in today’s rapidly developing process of globalization, foreign language teachers are given a number of tasks in their professional activities. In this article, the most important features of the teacher’s competencies in the qualitative and effective organization of foreign language classes are discussed and scientifically and theoretically proven, relying on the opinions of foreign Methodist scientists in this regard.